Metaphorical Meaning of Taylor Swift’s Reputation Album: A Semantic Approach - Vellicia Oktia Tanujaya; Budi Purnomo (Surakarta English and Literature Journal, 2023)
Taylor Swift is a famous singer-songwriter, and her songs are enjoyed by people worldwide. One of her well-known works is a studio album called Reputation. This album is composed of many metaphors as figurative language, which is sometimes hard to understand. However, to run the communication well, listeners have to understand the message the songwriter wants through this album. Due to this importance, the researchers studied the Metaphorical Meaning of Taylor Swift’s Reputation Album study. This study aims to examine the meaning of the metaphorical phrases in the album based on Leech’s metaphoric rule and Yule’s meaning theory. The data were analyzed by the qualitative method along with a questionnaire, as a part of the quantitative approach to support data validation, mainly filled by Taylor Swift fans and people who often listened to her songs. The research findings show that all denotative meanings are like the connotative ones in the sense of semantic properties, which are abstract and build patterns. The findings are expected to make listeners better know and understand the metaphors and their meanings in the Reputation Album.